Balloon pulmonary valvuloplasty with percutaneous transluminal mitral commissurotomy balloon in pulmonary stenosis - Adhikari, Chandra Mani; Shrestha, Manish; Kharel, Sushant; Bogati, Amrit; Prajapati, Dipanker (Journal of Advances in Internal Medicine, 2024)
Pulmonary stenosis is common and accounts for 5%–12% of all congenital heart diseases. Echocardiography is the mainstay for evaluating pulmonary stenosis due to its easy availability, reproducibility and non-invasive nature. American Heart Association/American College of Cardiology (AHA/ACC) guideline recommends balloon pulmonary valvuloplasty in patients with moderate to severe valvular pulmonary stenosis. Due to its advantages over other balloons, Inoue and Accura balloon, balloons especially designed for Percutaneous Transluminal mitral commissurotomy can be used for successful balloon pulmonary valvuloplasty.